Inclusive Education Policy for Children with Special Needs: A Review of Stakeholder Perceptions in Southeast Sulawesi - Mu'min, Sitti Aisyah; Yulita, Nourma; Assingkily, Muhammad Shaleh; Rasmi, Rasmi; Gazali, Marlina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Various previous studies have analyzed inclusive education policies for children with special needs. However, research that focuses on stakeholder perceptions has not been found. In Southeast Sulawesi, the implementation of inclusive education policies still faces various challenges, especially in terms of understanding and support from various stakeholders. This study aims to analyze the perceptions of stakeholders, including teachers, parents, education observers, and government officials, towards inclusive education policies for children with special needs in Southeast Sulawesi. To obtain data, a qualitative approach was used with a descriptive phenomenological study method. The research setting was at SMPN 1 Kendari, SMPN 2 Kendari, SMPN 1 Latambaga, Kolaka Regency. The selection of locations was based on pilot inclusive schools determined by the government. Data was obtained through interviews and documentation studies. Furthermore, the data were analyzed using data reduction, data display, and verification (conclusion stage). The results of the study indicate that although inclusive education policies in Southeast Sulawesi have been implemented, there are still gaps in understanding, training of educators, and the availability of adequate facilities. Stakeholders have varying views on the success of this policy, with some viewing it as a positive step, but others stating that the implementation of the policy is still limited and not fully effective. This study recommends increasing training for educators, providing more inclusive facilities, and more intensive socialization to all stakeholders so that the inclusive education policy can run optimally in Southeast Sulawesi